IBM Spectrum Virtualize HyperSwap SAN Implementation and Design Best Practices - Green, David; Fincher, Jordan (IBM Redbooks, 2020)
In this paper, we outline some IBM® Spectrum Virtualize HyperSwap® SAN implementation and design best practices for optimum resiliency of the SAN Volume Controller cluster. It provides IBM Spectrum® Virtualize HyperSwap and Stretched Cluster configuration details. Note: In this book, for brevity, we use HyperSwap to refer to both HyperSwap and Stretched Cluster. The documentation there details the minimum requirements. However, it does not describe the design of the storage area network (SAN) in detail, nor does it describe the recommended way to implement those requirements on a SAN. In this IBM Redpaper publication, we outline some of the best practices for SAN design and implementation that leads to optimum resiliency of the SAN Volume Controller (SVC) cluster, and we explain why each recommendation is made. This paper is SAN vendor-neutral wherever possible. Any mention of a specific SAN switch vendor, or terms used by a specific switch vendor, is made only where relevant to a specific context, and does not imply an endorsement of a specific switch vendor. Note: Some of the figures in this document might not depict redundant fabrics or storage configurations. This was done for simplicity, and it should be assumed that any recommendations made for fabric design assume that there are two redundant fabrics.